Using nisin-chitosan films enriched with rosemary extract on Listeria innocua, Escherichia coli O157:H7 and Pseudomonas aeruginosa in cold-smoked salmon during cold storage - Samyah D. Jastaniah (Applied Food Research)
This research aimed to assess the synergistic interaction of rosemary extract incorporated in nisin films or chitosan films for enriching edible films and their effects on Listeria innocua, L. monocytogenes, Escherichia coli O157:H7, and Pseudomonas aeruginosa inoculated in cold-smoked salmon (CSS) during cold storage. The study was designed to explore the effectiveness of these antimicrobial films in reducing bacterial load and ensuring food safety in CSS. A mixed culture cocktail of L. innocua, L. monocytogenes, E. coli O157:H7 and P. aeruginosa was inoculated on sliced of CSS followed by treatments the control, rosemary extract 5 % in nisin-films (T1), rosemary extract 5 % in chitosan-films (T2), rosemary extract 10 % in nisin-films (T3), rosemary extract 10 % in chitosan-films (T4). Approximately 2.53 Log10 CFU/g reductions in the number of E. coli O157:H7 and L. monocytogenes, while about 2.0 Log10 CFU/g in case of L. innocua and P. aeruginosa were found when samples treated with T1 and T2. A combination of T3 and T4 resulted in reduction in the count of the tested pathogenic bacteria ⁓ 3.55 to 4.56 Log CFU/g. The control samples had a total count of 7 Log10 CFU/g, but the nisin films enhanced with 10 % rosemary extract film reduced L. monocytogenes, L. innocua, P. aeruginosa, and E. coli O157:H7 to <10 CFU/g, while preserving total counts at <2.0 Log10 CFU/g. These findings suggest that cold-smoked films have the potential to be an environmentally sustainable option for food packaging. Specifically, these films can be intentionally engineered to incorporate antimicrobial agents, which serve as a protective barrier against the growth of harmful foodborne pathogens. By utilizing natural and biodegradable materials, such as chitosan, in the formulation of these films, they not only provide an effective method of extending the shelf life of perishable food products but also contribute to reducing the environmental impact of traditional plastic packaging. As a result, cold-smoked films could offer a promising, eco-friendly alternative that helps maintain food safety while minimizing waste and promoting sustainability in the food industry.